2019
DOI: 10.14742/ajet.5483
|View full text |Cite
|
Sign up to set email alerts
|

Online learning for university students on the autism spectrum: A systematic review and questionnaire study

Abstract: Online course delivery is increasingly being used by universities to deliver accessible and flexible learning environments. As this mode of delivery grows it is important to consider the equity of the learning experience for all students. As online delivery may reduce challenges and stressors present in face-to-face delivery, it could be suggested that it may promote student learning for specific student groups, including those with a diagnosis on the autism spectrum. However, little is known about the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…Study Findings Adams et al, (2019) Individuals with ASD stated that asking questions in an OLE is challenging, and such environments are more insecure compared to facetoface education. On the other hand, they provided positive opinions regarding the flexibility and usability of the environment.…”
Section: Table 4 Findings On Resultsmentioning
confidence: 98%
“…Study Findings Adams et al, (2019) Individuals with ASD stated that asking questions in an OLE is challenging, and such environments are more insecure compared to facetoface education. On the other hand, they provided positive opinions regarding the flexibility and usability of the environment.…”
Section: Table 4 Findings On Resultsmentioning
confidence: 98%
“…Another important action to be taken was assisting students with special needs and their parents with technology support (M = 1.91, SD = 0.284). As underscored by Adams et al (2019), context-appropriate usage of technologies and tools and lack of scaffolding for students about the best way to use those technologies may affect how successfully students engage with their learning environments. Lastly, providing psychological counseling and guidance to parents (M = 1.87, SD = 0.340) was the action stressed by respondents.…”
Section: Actions For Students With Special Needs and Their Familiesmentioning
confidence: 99%
“…Even though it is emphasised in various instances that accessibility is advantageous for all students, hardly any studies can be found which explicitly address accessibility when examining the use of digital media (Grosch, 2012;Schmid et al, 2017;Steffens et al, 2017). Scientific work in the higher education context that explicitly addresses media accessibility is often conceptual rather than empirical (Burgstahler, 2015b;Fichten et al, 2020) or focuses on singular types of impairment, such as autism (Adams et al, 2019), intellectual impairment (Arachchi et al, 2017) or visual impairment (Köhlmann, 2017). However, since accessibility and usability directly impact the pedagogical effectiveness of e-learning systems and resources for all learners, especially those with disabilities, both aspects should be considered in all e-learning projects equipollent (Cooper et al, 2007).…”
Section: State Of the Artmentioning
confidence: 99%